2010
DOI: 10.1080/10683160902971055
|View full text |Cite
|
Sign up to set email alerts
|

How do sex offenders think the police should interview to elicit confessions from sex offenders?

Abstract: The purpose of this study is to explore sex offenders' perceptions of how the police should interview suspected sex offenders to facilitate confessions, and to investigate whether there is a relationship between sex offenders' perceptions of how the police interviewed them and their decisions to confess or deny. Forty-three convicted sex offenders were interviewed using two 35-item questionnaires that contained five questions on each of seven interviewing strategies. An additional 20 violent offenders were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 34 publications
11
56
1
Order By: Relevance
“…While a number of areas requiring progress have been discussed, overall interviewers adopted an approach that appeared ethical and humane. This is consistent with the current guidelines for interviewing suspects in Australia and the UK (Gudjonsson and Sigurdsson 2000, Holmberg and Christianson 2002, Beauregard et al 2010, Kebbell et al 2010) and with Soukara et al's (2009) findings. Despite commonly held misconceptions about the dramatic nature of police interviews from popular television programs, our study supports the assertions of Dixon (2009), who argued that interviewing can be improved by interviewers practicing everyday social skills in the interview room, such as good eye-contact, active listening and appropriate follow-up questioning.…”
Section: Discussionsupporting
confidence: 89%
“…While a number of areas requiring progress have been discussed, overall interviewers adopted an approach that appeared ethical and humane. This is consistent with the current guidelines for interviewing suspects in Australia and the UK (Gudjonsson and Sigurdsson 2000, Holmberg and Christianson 2002, Beauregard et al 2010, Kebbell et al 2010) and with Soukara et al's (2009) findings. Despite commonly held misconceptions about the dramatic nature of police interviews from popular television programs, our study supports the assertions of Dixon (2009), who argued that interviewing can be improved by interviewers practicing everyday social skills in the interview room, such as good eye-contact, active listening and appropriate follow-up questioning.…”
Section: Discussionsupporting
confidence: 89%
“…According to Beauregard et al (2010), sexual offenders may be unique; less likely to confess their crimes because of the objective and subjective severity of these offences, personal experiences of humiliation and shame during the interrogation, and the police officers' negative demeanor during interrogation (Beauregard et al 2010). Further, several studies (e.g., Holmberg and Christianson 2002;Kebbell et al 2010) have demonstrated that different interviewing techniques are used when interrogating sexual as opposed to violent offenders. Therefore, we examined the type of offense as one factor influencing suspects' confessions.…”
Section: Factors Related To Confessionsmentioning
confidence: 95%
“…When the evidence is strong, suspects are more likely to confess (Cassell and Hayman 1996;Moston et al 1992). Certain police techniques such as adoption of a humanitarian approach (Holmberg and Christianson 2002;Kebbell et al 2010), minimization and maximization (Horgan et al 2012), and showing understanding of the suspect's actions (Kebbell et al 2010) also help to elicit confessions from guilty suspects.…”
Section: Factors Related To Confessionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Two distinct styles are referred to in the recent literature, namely humane or dominant (see Holmberg & Christianson, 2002;Kebbell, Alison, Hurren, & Mazerolle, 2010;Kebbell, Hurren, & Mazerolle, 2006). Dominant interviewing is characterised by aggressive and hostile interviewer behaviour, whereas humane interviewing is marked by a less confrontational, more empathic and respectful attitude by the interviewer.…”
Section: Introductionmentioning
confidence: 97%